Hearing treshold before and after middle ear surgery in chronic suppurative otitis media (CSOM) - Bambang Udji Djoko Rianto*; . Suwardi; Edhie Samodra (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Hearing loss is a common symptom in chronic suppurative otitis media (CSOM),often cause social communication disturbance. Canal wall up tympanoplastyand canal wall down tympanoplasty are surgery procedures for managing thisdisease that no response to convensional treatment. These surgery proceduresshould consider to hearing function impact. The aim of this study was to evaluatethe difference hearing threshold between before and after middle ear surgeryon CSOM patients. It was an historical cohort study conducted from January2015 to December 2016 involving CSOM patients who underwent canal wall uptympanoplasty surgery and canal wall down tympanoplasty in The Otology Division,Departement of Ear, Nose, Throat, Head and Neck Health, Dr. Sardjito GeneralHospital, Yogyakarta. The inclusion criteria included basic data, diagnostics,surgery reports, and audiometry results before and 3 months postoperatively,while the exclusion criteria were not complete medical record data. Total of 64patients with CSOM were involved in this study consisting of 32 patients whounderwent canal wall up tympanoplasty and 32 patients who underwent canal walldown tympanoplasty. Significantly different in the increasing of hearing thresholdbetween before and after canal wall up tympanoplasty surgery compared to thecanal wall down tympanoplasty was observed (p = 0.021). In addition, surgicaltechnique was the main factor affecting postoperative hearing threshold in CSOMpatients (p < 0.05). In conclusion, the increasing of hearing threshold in CSOMpatients underwent canal wall up tympanoplasty surgery is better than those underwentcanal wall down tympanoplasty.